Van der Woude syndrome with sensorineural hearing loss, large craniofacial sinuses, dental pulp stones, and minor limb anomalies: Report of a four-generation Thai family - Kantaputra P.N. (2014)
A four-generation Thai family affected with Van der Woude syndrome is reported. The disorder appeared to be originally inherited from a person who was half Thai and half Pakistani. The lip lesions found in this family were varied and did not appear to be related to other phenotypes. There were some clinical manifestations possibly specific for the condition in this family. They included sensorineural hearing loss, prominent frontal bone, large frontal/sphenoidal/ maxillary sinuses with increased mastoid air cells, long tooth roots, dental pulp stones, ankyloglossia, brachydactyly of hands, brachyphalangy, and hyperphalangy of toes, and single flexion crease of the fifth fingers. Fluorescence in situ hybridization analysis revealed no visible deletion at a 1q32-41 region. © 2002 Wiley-Liss, Inc.